KOREKSI TERHADAP PENGUKURAN POLUTAN DI UDARA DAN DAMPAKNYA TERHADAP KESEHATAN - Husaini Husaini (Lambung Mangkurat, 2015)
AbstractUnderstanding the reaction of various pollutants in the air until today continues to grow, even hardly find information about the results of the reaction of various air pollutants standard. The aim of research to analyze and correction of the measurement of various air pollutants as well as the impact on health of blacksmith. The case study done on 38 blacksmith and 38 working units in Hulu Sungai Selatan South Kalimantan with observational analytic approach along with sampling of air pollutants and blood sampling as well as examination of pulmonary function of workers. The results showed a decrease in lung function and abnormalization workers immune response, as a result of exposure to various air pollutants, so it is very difficult to determine and predict because it is caused by pollutants singly or may be caused from the various reactions of these pollutants, for that, the correction need on the measurement and analysis of air pollutants that made so far, including its impact on the human body. The benefits of this research as a form of correction to use the Threshold Limit Value (TLV) and measuring air pollutants, including the impact of the target organ in the human body.Keywords: Measurements correction, pollutants, lung function, immune response